Experiences from 40 years of muskox (Ovibos moschatus) farming in Norway - Blix, Arnoldus Schytte; Ness, John; Lian, Hans (Rangifer, 2011)
Experiences from the management of a semi-domesticated herd of muskoxen, mostly on an island outside Tromsø ( 70º N; 19º E), over a period of 40 years have been collected, and data on husbandry practices, reproduction, diseases and longevity are presented and discussed.